Does Democracy Reduce Corruption in Indonesia? - Azwar Azwar; Achmat Subekan (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze the long and short-run impact of democracy on corruption in Indonesia. This study used the method of Autoregressive Distributed Lag (ARDL) and dynamic Error Correction Model (ECM) technique during the year of 1995-2020 with secondary data from The Economist Intelligence Unit (EIU), The Global Economy and World Bank’s World Development Indicators (WDI), and Transparency International. The results of the study indicated that democracy has significant effects on the level of corruption only in the long run. In the long run, the results show that the impact of democracy is significant at a 1% significance level and decreases the amount of corruption in Indonesia. A 1% change in democracy and other factors are considered equal, which will change the corruption level by approximately 0.2%. The results imply that political stability associated with democracy will result in the corruption index. In other words, the results suggest that democracy reduces corruption. From a policy point of view, this means that developing democratic institutions should be part of strategies to reduce corruption.